The value relevance of deferred tax assets: An empirical analysis of German HDAX-listed companies - Jochen Zimmermann (Accounting and Financial Control, 2024)
Deferred taxes emerge from timing differences in recognizing income and expenses between commercial and tax financial statements. However, the capitalization of deferred tax assets remains contentious, with questions raised about their value relevance to investors. This study aims to investigate the informational value and economic significance of deferred tax assets in financial statements prepared in accordance with both German commercial law (HGB) and International Financial Reporting Standards (IFRS). The analysis is based on financial data from 1,066 firm-year observations of HDAX-listed companies from 2000 to 2022. Using an Ordinary Least Squares (OLS) regression model, the study examines the relationship between deferred tax assets and the market value of equity. Key financial variables, including research and development expenses, deferred tax liabilities, net income, and the market-to-book ratio, are incorporated to provide a comprehensive assessment of deferred tax asset relevance in capital markets. The results demonstrate that deferred tax assets have a negligible impact on the market value of companies, with no statistically significant effect detected. Conversely, research and development costs, as well as net income, exhibit a strong positive influence on firm valuation. These findings suggest that deferred tax assets serve largely as an accounting mechanism, lacking informational value for investors.